Mathematical model and algorithm for determining the relative consumption of electricity - U. Rakhmonov, Ikromjon; A. Jalilova, Dinora (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: the relevance of the work is to determine the factors affecting the consumption of electricity in the textile industry, especially in spinning enterprises. Determining the factors affecting the consumption of electricity in any industrial sector and industrial enterprises leads to an increase in the efficiency of electricity consumption and savings in the use of electricity, as well as the rational use of fuel and energy resources. Factors affecting electricity consumption are divided into several groups. Studying them in groups of influence in each field will facilitate the work on energy efficiency. In particular, in this work, the factors affecting the electricity consumption of spinning enterprises were divided into 4 groups, and 10 factors from these groups were selected as the factors affecting the electricity consumption. At the same time, the degree of impact of the isolated factors was selected using the expert evaluation method and checked on the basis of regression analysis, and the mathematical model and algorithm of the comparative consumption of electricity were developed. Aim: consists of developing a mathematical model and algorithm for determining the comparative consumption of electricity by determining the factors affecting electricity consumption. Methods: the expert assessment method was used to determine the factors affecting electricity consumption, correlation and regression analysis was used to develop the mathematical model and algorithm for determining the comparative electricity consumption, and Fisher's criterion and relative error methods were used to assess its adequacy. Results: A mathematical model and algorithm of the comparative consumption of electricity were developed with the help of determining the factors influencing the consumption of electricity in yarn-spinning enterprises. Also, when the adequacy of the developed mathematical model is checked using Fisher's criterion and relative error methods, it was developed that the values ​​of the mathematical model are less than 244, the table value of Fisher's criterion is less than 432, and the relative error of the model is in the range of [-0.4÷2.19%] justifies the adequacy of the model.